The case for intervening in bankers' pay - Thanassoulis, J (University of Oxford, 2011)
This paper studies banker remuneration in a competitive market for banker talent. I model, and then calibrate, the default risk of the banks generated by investments and remuneration pressures. Competing banks prefer to pay their banking staff in bonuses and not in wages as risk sharing on the remuneration bill is valuable. But competition for bankers generates a negative externality driving up rival banks' default risk. Optimal financial regulation involves an appropriately structured limit on the proportion of the balance sheet used for bonuses. However stringent bonus caps are value destroying, default risk enhancing and cannot be optimal for regulators who control only a small number of banks. The paper allows an assessment of the intellectual arguments behind widespread calls to regulate the pay of bankers. The paper uses US data to calibrate the analysis and demonstrate the significant contribution of remuneration to default risk.